Effect of oral rehydration solution versus spring water intake during exercise in the heat on muscle cramp susceptibility of young men - Wing Yin Lau; Haruyasu Kato; Kazunori Nosaka (Taylor & Francis Group, 2021)
Background Muscle cramp is a painful, involuntary muscle contraction, and that occurs during or following exercise is referred to as exercise-associated muscle cramp (EAMC). The causes of EAMC are likely to be multifactorial, but dehydration and electrolytes deficits are considered to be factors. This study tested the hypothesis that post-exercise muscle cramp susceptibility would be increased with spring water ingestion, but reduced with oral rehydration solution (ORS) ingestion during exercise. Methods Ten men performed downhill running (DHR) in the heat (35-36 °C) for 40-60 min to reduce 1.5-2% of their body mass in two conditions (spring water vs ORS) in a cross-over design. The body mass was measured at 20 min and every 10 min thereafter during DHR, and 30 min post-DHR. The participants ingested either spring water or ORS for the body mass loss in each period. The two conditions were counter-balanced among the participants and separated by a week. Calf muscle cramp susceptibility was assessed by a threshold frequency (TF) of an electrical train stimulation to induce cramp before, immediately after, 30 and 65 min post-DHR. Blood samples were taken before, immediately after and 65 min after DHR to measure serum sodium, potassium, magnesium and chroride concentrations, hematocrit (Hct), hemoglobin (Hb), and serum osmolarity. Changes in these varaibles over time were compared between conditions by two-way repeated measures of analysis of variance. Results The average (±SD) baseline TF (25.6 ± 0.7 Hz) was the same between conditions. TF decreased 3.8 ± 2.7 to 4.5 ± 1.7 Hz from the baseline value immediately to 65 min post-DHR for the spring water condition, but increased 6.5 ± 4.9 to 13.6 ± 6.0 Hz in the same time period for the ORS condition (P < 0.05). Hct and Hb did not change significantly (P > 0.05) for both conditions, but osmolarity decreased (P < 0.05) only for the spring water condition. Serum sodium and chloride concentrations decreased (< 2%) at immediately post-DHR for the spring water condition only (P < 0.05). Conclusions These results suggest that ORS intake during exercise decreased muscle cramp susceptibility. It was concluded that ingesting ORS appeared to be effective for preventing EAMC.